Socioeconomic Status and Postpartum Depression Risk After the Dobbs v Jackson Women s Health Organization Decision, Based on State Trigger Laws - Sepulveda-Pizarro, F (American Medical Association, 2026)
This cohort study analyzes associations of state-level abortion bans enacted after the Dobbs v Jackson Women s Health Organization decision with incidence of postpartum depression among individuals with varying levels of socioeconomic status (SES). QuestionAre state abortion bans enacted after the Dobbs v Jackson Women s Health Organization decision associated with increased rates of postpartum depression (PPD) among Medicaid enrollees, based on socioeconomic status (SES)?FindingsThis cohort study including 102 597 individuals pre-Dobbs and 61 113 individuals post-Dobbs found that women with low SES who lived in states with abortion bans experienced a significant 9.0% relative increase in PPD diagnoses after Dobbs vs those in states without bans. No differences in rates of PPD after Dobbs were observed among women in trigger vs nontrigger states living in middle- or high-SES areas.MeaningThis study found that post-Dobbs abortion bans were disproportionately associated with an increased PPD risk among individuals in low-SES communities, amplifying existing health disparities. ImportanceThe 2022 Supreme Court decision in Dobbs v Jackson Women s Health Organization resulted in immediate abortion bans or severe restrictions in 22 US states. While mental health consequences of restricted abortion access have been suggested, their distribution across socioeconomic strata remain unclear for postpartum depression (PPD) among Medicaid populations.ObjectiveTo assess associations of state-level abortion bans enacted after Dobbs with the incidence of PPD, focusing on socioeconomic status (SES) differences.Design, Setting, and ParticipantsThis retrospective cohort study used a difference-in-differences (DD) analysis for Medicaid claims data from Kythera Labs (approximately 60% of US Medicaid population) from January 2019 to December 2024. Women and adolescents aged 12 to 55 years with pregnancies resulting in live births or stillbirths were stratified into SES terciles based on zip code-level census data.ExposureState-level abortion bans or restrictions implemented after Dobbs, defined by residence in trigger law states.Main Outcomes and MeasuresThe primary outcome was incidence of PPD within 12 months following delivery, identified through validated claims-based algorithms.ResultsThe study comprised 102 597 individuals pre-Dobbs (mean [SD] age, 27.21 [5.82] years; 47 305 individuals in trigger states and 55 292 individuals in nontrigger states) and 61 113 individuals post-Dobbs (mean [SD] age, 27.48 [5.92] years; 30 451 individuals in trigger states and 30 662 individuals in nontrigger states). Individuals in trigger states were younger than individuals in nontrigger states both pre-Dobbs (mean [SD] age, 26.53 [5.69] years vs 27.97 [5.84] years) and post-Dobbs (mean [SD] age, 26.61 [5.77] years vs 28.34 [5.94] years). Both pre- and post-Dobbs, individuals in trigger states were more likely to reside in rural areas (pre-Dobbs: 10 562 individuals [22.33%] vs 10 079 individuals [18.23%]; post-Dobbs: 6739 individuals [22.13%] vs 5220 individuals [17.02%]) and low-SES areas (pre-Dobbs: 20 136 individuals [42.57%] vs 13 771 individuals [24.91%]; post-Dobbs: 12 924 individuals [42.44%] vs 7283 [23.75%]); they were less likely to have obstetrical complications (pre-Dobbs: 31 243 individuals [66.05%] vs 42 780 individuals [77.37%]; post-Dobbs: 21 052 individuals [69.13%] vs 24 577 individuals [80.15%]) or maternal complications (pre-Dobbs:7732 individuals [16.34%] vs 10 839 of individuals [19.60%]; post-Dobbs: 5779 of 30 451 individuals [19.04%] vs 6508 individuals [21.17%]). Women with lowest SES residing in trigger states experienced a 9.0% relative increase in PPD diagnoses post-Dobbs vs similar women in nontrigger states (DD coefficient, 0.090; 95% CI, 0.035-0.146; P = .001). No associations were observed in middle or high SES groups.Conclusions and RelevanceIn this cohort study, state-level abortion bans following Dobbs were associated with a disproportionate increase in the risk of PPD among women and adolescents in low-SES communities. These findings underscore the need for targeted mental health support and policy interventions to mitigate the unequal burden of such legislation on vulnerable populations.